CAPE VERDEAN CREOLE: LINGUISTIC CHANGE, ORTHOGRAPHIC POLITICS, AND EDUCATIONAL CHALLENGES - Dal'Ava, Lucas Manca (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2025)
This study examines Cape Verdean Creole (CVC) through contact linguistics, phonology, and language policy frameworks. Based on 2014 fieldwork and literature review, it traces CVC’s evolution from a 15th-century Portuguese-lexified variety to a pluricentric language with nine dialects shaped by geographic and sociolinguistic factors. Phonological changes include loss of [dʒ] in favor of [ʒ], nasal diphthong development, and syllabic simplification. The sociopolitical dynamics surrounding ALUPEC orthography highlight tensions between linguistic unity and dialectal variation. Field observations reveal Brazilian cultural influence and policy challenges, such as Creole’s marginalization in education despite its broad vernacular use. Findings problematize traditional creolization models, proposing “strategic hybridization” as a framework to understand CVC’s selective feature adoption. The study emphasizes the urgency of inclusive language policies that recognize Creole as a full language, balancing standardization with dialectal diversity to reinforce linguistic equity and national identity.